Enhanced microwave conversion of oil palm mesocarp fiber to levulinic acid using H3PW12O40-Nb2O5 functionalized carbon cryogel derived from lignin hydrogel - Azlan, Nadiah Syafiqah Mohd; Yap, Chiew Lin; Tiong, Yong Wei; Gan, Suyin; Rahman, Mohd Basyaruddin Abdul (Elsevier, 2024)
This study aims to transform a hydrogel functionalized with phosphotungstic acid and niobium oxide into a carbon cryogel, serving as an efficient catalyst for converting oil palm mesocarp fiber to levulinic acid using microwave technology. The lignin-gum hydrogel exhibits desirable properties, including a moderately high swelling ratio (10.3 g/g), water absorption capacity (220 ), robust crosslinking (71.7 yield), and notable compressive strength (0.8 MPa at 90 strain). The swollen state of the hydrogel, with an average pore size of 2.5–4.0 μm, enhances microwave energy penetration into the biomass matrix. This work offers an alternative approach to enhance biomass conversion, utilizing lignin-derived cryogel with impressive levulinic acid yield (18.4 ) and conversion efficiency (81 ). Testing the hydrogel properties is crucial for ensuring optimal performance during the upgrade to carbon cryogel.